Long-term consequences of the misuse of ivermectin data - Alvarez-Moreno, Carlos; Cassell, Jackie A; Donkor, Claudia M; Head, Michael G; Middleton, Jo; Pomat, William; Saka, Bayaki; Yirgu, Robel (The Lancet infectious diseases, 2021)
On March 31, 2021, WHO advised that ivermectin should only be used within clinical trials and not as part of routine clinical practice.4 This advice was followed by the manufacturer, Merck, that stated on Feb 4, 2021, that there is “no meaningful evidence for clinical activity or clinical efficacy in patients with COVID-19 disease”.5 Despite this, ivermectin is being routinely used in some Latin American settings amid recommendations from some governments and health professionals.6 In July, 2021, a number of scientists reviewed and reported detailed clinical trial data for use of ivermectin for COVID-19.7 Their commentaries, which were not peer-reviewed, highlighted extensive inconsistencies within the trial data. Ivermectin itself has been the subject of a widely reproduced but unsubstantiated link to mortality in older people in care homes that still deters clinical use in some settings (including the UK).10 Sustained misinformation can lead to diversion of limited health-care and government resources to addressing rumours rather than making genuine public heath progress. Proactive health promotion and education is needed right now to ensure that locally trusted actors and communicators (including, but not limited to, health-care workers) are aware of the uncertainty around the ivermectin evidence base for managing COVID-19, and that it remains a vital medicine for managing neglected tropical disease.